Adventure Therapy : Theory, Research, and Practice - Gass, Michael A., ....-; Gillis, Lee, ....-; Russell, Keith C., ....- (New York : Routledge, 2020)
This revised text describes the theory substantiating adventure therapy, demonstrates best practices in the field, and presents research validating the immediate and long-term effects of adventure therapy. A leading text in the field of adventure therapy, outdoor behavioral healthcare, and wilderness therapy, the book is written by three professionals who have been at the forefront of the field since its infancy. This new edition includes fully updated chapters to reflect the immense changes in the field since the first edition was written in 2010. It serves to provide information detailing what is occurring with clients as well as how it occurs. This book provides an invaluable reference for the seasoned professional and is a required source of information and examination for the beginning professional. It is a great training resource for adventure therapy practices in the field of mental health.